Performance and Meat Quality of Local Sheep Administered with Feed Additive Containing Probiotic and Organic Mineral Complex - H Herdian; A Sofyan; A A Sakti; H Juendra; M F Karimy; A E Suryani; E Damayanti; L Istiqomah (Media Peternakan, 2013)
The experiment was conducted to evaluate the effect of probiotic and organic mineral complex (POMC) administration on performance and meat quality of local sheep. In this study, 6 sheep with an average initial body weight of 12.67±0.81 kg were arranged in a completely randomized design with 2 treatments and 3 replications. The treatments were T0: basal diet (control) and T1: basal diet + POMC. The basal diet consisted of forage and concentrate (60:40) with dry matter of feed intake as much as 5% of body weight. Dose of POMC used in this study was 15 g/d/head. The POMC contained lactic acid bacteria, i.e. Lactobacillus sp. (1x108 cfu/g) and S. cereviseae incorporated with micromineral Co (2 ppm), Cu (100 ppm), Fe (2.5 ppm), I (110 ppm) and Mn (100 ppm). The experimental period lasted for 11 wk (1 wk for adaptation and 10 wk for data collection). Data were analyzed using t-Student statistical test to compare the treatments. The results showed that POMC administration did not affect the body weight gain (BWG) (7.46 kg) compared to control (7.13 kg) while concentrate consumption (26.9 kg) of POMC was lower than the control (28.6 kg). Meanwhile POMC administration did not affect the meat quality (pH, moisture, cooking loss and tenderness), whereas the meat cholesterol was lower (34.25 mg/100g) than the control (38.87 mg/100g). It is concluded that administration of probiotic lactic acid bacteria combined with organic minerals decreases concentrate consumption and thereby potentially increases the animals energy utilization efficiency. In addition, the treatment also decreases the meat cholesterol content of local sheep.